Potentials of Implementation of Sharia Principles in the Tourism Sector of Batu City, East Java - Zaki, Irham; Hamida, Gautsi; Cahyono, Eko Fajar (UPT Publikasi Ilmiah UNISBA, 2020)
The main objective of this research is to see the potential that supports the implementation of sharia principles in the Batu City tourism sector. The tourism sector studied consists of hotels, restaurants and food, travel agencies and tourist areas. The next objective is to see the economic benefits that will be produced in the future with the application of sharia principles in the tourism sector. This study uses descriptive qualitative methods conducted by interviews, observations and questionnaire tools to see the response generated through a Likert scale. The results of this study indicate that parties related to the tourism sector provide a positive response to the application of sharia principles in the tourism sector, which will provide economic benefits for industry players, the public, and the government.